No Evidence for a Decrease in Physical Activity Among Swiss Office Workers During COVID-19: A Longitudinal Study - Aegerter, Andrea Martina; Deforth, Manja; Sjøgaard, Gisela; Johnston, Venerina; Volken, Thomas; Luomajoki, Hannu; Dratva, Julia; Dressel, Holger; Distler, Oliver; Melloh, Markus; Elfering, Achim; , the NEXpro Collaboration Group; et al. (Frontiers in Psychology, 2021)
Purpose: The COVID-19 lockdown interrupted normal daily activities, which may have led to an increase in sedentary behavior. The aim of this study was to investigate the effect of the COVID-19 pandemic on the level of physical activity among Swiss office workers. Methods: Office workers from two Swiss organizations, aged 18-65 years, were included. Baseline data from January 2020 before the COVID-19 pandemic became effective in Switzerland were compared with follow-up data during the lockdown phase in April 2020. Levels of physical activity were assessed using the International Physical Activity Questionnaire. Paired sample t-tests or Wilcoxon signed-rank test were performed for statistical analysis. Results: Data from 76 participants were analyzed. Fifty-four participants were female (71.1%). The mean age was 42.7 years (range from 21.8 to 62.7) at baseline. About 75% of the participants met the recommendations on minimal physical activity, both before the COVID-19 pandemic and during the lockdown. Weak statistical evidence for a decline in total physical activity in metabolic equivalent of task minutes per week (MET min/week) was found (estimate = -292, 95% CI from – ∞ to 74, p-value = 0.09), with no evidence for a decrease in the three types of activity: walking (estimate = -189, 95% CI from – ∞ to 100, p-value = 0.28), moderate-intensity activity (estimate = -200, 95% CI from – ∞ to 30, p-value = 0.22) and vigorous-intensity activity (estimate = 80, 95% CI from – ∞ to 460, p-value = 0.74). Across the three categories ‘high’, ‘moderate’ and ‘low’ physical activity, 17% of the participants became less active during the lockdown while 29% became more active. Conclusion: The COVID-19 pandemic did not result in a reduction in total physical activity levels among a sample of Swiss office workers during the first weeks of lockdown. Improved work-life balance and working times may have contributed to this finding.